Preclinical verification of the efficacy by targeting peptide-linked liposomal nanoparticles for hepatocellular carcinoma therapy. (30th December 2019) - Wu, Cheng-Der; Lee, Jen-Chieh; Wu, Hang-Chung; Lee, Chung-Wei; Lin, Chih-Feng; Hsu, Ming-Chen; Lin, Chin-Tarng
The purpose of this study was to investigate the efficacy of targeting peptides chemotherapy to overcome adverse event in the conventional chemotherapy for human hepatocellular carcinoma. Previously we reported several cancer-targeting peptides that bind specifically to cancer cells and their vascular endothelia: L-peptide (anti-cancer cell membrane), RLLDTNRPLLPY; SP-94-peptide (anti-hepatoma cell membrane), SFSHHTPILP; PC5-52-peptide (anti-tumor endothelia), SVSVGMKPSPRP; and control peptide, RLLDTNRGGGGG. In this study, these peptides were linked to liposomal iron oxide nanoparticles to localize the targeted tumor cells and endothelia, and to dextran-coated liposomal doxorubicin (L-D) to treat nonobese diabetic severe combined immunodeficient mice bearing hepatoma xenografts. Our results showed that L-peptide-linked liposomal doxorubicin could inhibit tumor growth with very mild adverse events. Use of the control peptide led to a decrease in the xenograft size but also led to marked apoptotic change in the visceral organ. In conclusion, L-peptide-linked liposomal doxorubicin, SP-94-peptide, and PC5-52-peptide can be used for the treatment of hepatoma xenografts in nonobese diabetic severe combined immunodeficient mice with minimal adverse events.